Ethanol-induced phospholipase C activation is inhibited by phorbol esters in isolated hepatocytes. - Hoek, J B (1988)
Ethanol causes a transient activation of the phosphoinositide-specific phospholipase C in intact hepatocytes and mimics the action of receptor-mediated agonists [Hoek, Thomas, Rubin & Rubin (1987) J. Biol. Chem. 262, 682-691]. Preincubation of the hepatocytes with phorbol esters which activate protein kinase C prevented this effect of ethanol: phorbol ester treatment inhibited the ethanol-induced phosphorylase activation, the increase in intracellular free Ca2+ concentrations measured in quin 2-loaded hepatocytes, and the changes in concentrations of inositol phosphates, phosphoinositides and phosphatidic acid. Several lines of evidence indicate that these effects were mediated by protein kinase C. Phorbol esters acted in a concentration range where they activate protein kinase C; phorbol esters that do not activate protein kinase C were not effective in inhibiting the effects of ethanol. The permeant diacylglycerol oleoyl-acetylglycerol also inhibited the effects of ethanol, but other diacylglycerols were not effective in the intact cells. The inhibition of ethanol-induced Ca2+ mobilization by phorbol esters was prevented by preincubating the cells with the protein kinase C inhibitors 1-(5-isoquinolinesulphonyl)-2-methylpiperazine (H7) and sphingosine. H7 also enhanced the Ca2+ mobilization induced by ethanol in cells that were not pretreated with phorbol esters, indicating that the transient nature of the ethanol-induced Ca2+ mobilization may be due to an activation of protein kinase C caused by the accumulation of diacylglycerol. These data support a model whereby ethanol activates the phosphoinositide-specific phospholipase C, possibly by affecting receptor-G-protein-phospholipase C interactions in the membrane.